MYCN amplification predicts poor outcome for patients with supratentorial primitive neuroectodermal tumors of the central nervous system. (26th January 2014) - Gessi, Marco; von Bueren, André O.; Treszl, Andras; Mühlen, Anja zur; Hartmann, Wolfgang; Warmuth-Metz, Monika; Rutkowski, Stefan; Pietsch, Torsten
Abstract: Background: Primitive neuroectodermal tumors of the central nervous system (CNS-PNETs) are a rare group of neoplasms occurring in the CNS that includes supratentorial CNS-PNETs, medulloepitheliomas, and ependymoblastomas. While ependymoblastomas frequently carry chromosome 19q13.41 amplification and show aggressive clinical behavior, the biological mechanisms and molecular alterations contributing to the pathogenesis of supratentorial CNS-PNETs remain poorly understood. Moreover, genetic alterations suitable for molecular risk stratification are undefined to date. Methods: In order to identify possible molecular markers, we performed multiplex ligation-dependent probe amplification (MLPA) and molecular inversion probe (MIP) analysis on DNA samples of 25 supratentorial CNS-PNETs (median age, 5.35 years; range, 2.41–17.28 years). Tumors with ependymoblastic rosettes (ependymoblastoma/ETANTR) and LIN28A positivity were excluded. Results: MLPA and MIP analysis revealed large losses of genomic material of chromosomes 3, 4, 5, and 13, while frequent gains affected chromosomes 1, 17, 19, 20, and 22. High copy number gains (amplifications) were found in particular at chromosomes 2p24.3 ( MYCN, n = 6 cases) and 4q12 ( n = 2 cases). Patients with tumors harboring 2p gain or MYCN amplification showed unfavorable overall survival ( P = .003 and P = .001, respectively).These markers were independent of the presence of metastases, which was indeed a clinical factor associated with poor overall survival ( P = .01) in this series. Conclusions: In the era of the personalized neuro-oncology, the identification of these molecular prognostic markers associated with patient outcome may represent a significant step towards improved patient stratification and risk-adapted therapeutic strategies for patients suffering from supratentorial CNS-PNETs.